2023
DOI: 10.3390/app13169402
|View full text |Cite
|
Sign up to set email alerts
|

Improved Sea Ice Image Segmentation Using U2-Net and Dataset Augmentation

Yongjian Li,
He Li,
Dazhao Fan
et al.

Abstract: Sea ice extraction and segmentation of remote sensing images is the basis for sea ice monitoring. Traditional image segmentation methods rely on manual sampling and require complex feature extraction. Deep-learning-based semantic segmentation methods have the advantages of high efficiency, intelligence, and automation. Sea ice segmentation using deep learning methods faces the following problems: in terms of datasets, the high cost of sea ice image label production leads to fewer datasets for sea ice segmentat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 20 publications
(21 reference statements)
0
5
0
Order By: Relevance
“…However, it may introduce redundant and ineffective semantic information. Additionally, the structure built upon RSU is quite flexible and can be trained from scratch without the need for a pretrained backbone; it has minimal performance loss [32]. Ge et al [33] proposed an extraction method for large-scale PV power plants.…”
Section: Semantic Segmentation Networkmentioning
confidence: 99%
See 2 more Smart Citations
“…However, it may introduce redundant and ineffective semantic information. Additionally, the structure built upon RSU is quite flexible and can be trained from scratch without the need for a pretrained backbone; it has minimal performance loss [32]. Ge et al [33] proposed an extraction method for large-scale PV power plants.…”
Section: Semantic Segmentation Networkmentioning
confidence: 99%
“…CBAM combines the Channel Attention Module (CAM) and Spatial Attention Module (SAM) in a cascaded manner. As for CAM, Global Average Pooling (GAP) and Global Max Pooling (GMP) are firstly used to compress the spatial dimensions of the input features and condense spatial information [32]. Then, the correlation between channels is modeled through a Multilayer Perceptron (MLP) and the Sigmoid activation function.…”
Section: Spatial Attention Mechanism and Channel Attention Mechanismmentioning
confidence: 99%
See 1 more Smart Citation
“…Although deep learning has demonstrated its significant practical utility in various fields such as image processing, medical diagnosis, and speech recognition [16][17][18], the performance of deep learning models always relies heavily on data-driven conditions. In real-world applications, the inherent scarcity of abnormal sound data makes it difficult to meet this condition.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the model maintains high resolution as it becomes deeper while minimizing video memory overhead and computational requirements. Comparative experiments with multiple network models have demonstrated that U 2 -Net enhances accuracy, making it a suitable choice for extracting the features of the calving front[40,56].2.3.2. U -Net Architecture and Post-Processing U 2 -Net, a target detection model based on the traditional U-Net, is utilized in this study.…”
mentioning
confidence: 99%